Update on the Stock and Supply of Health Services Researchers in the United States. (4th June 2018) - Frogner, Bianca K.
Abstract : Objective: This study examines the stock and supply including educational pipeline of health services researchers (HSRers) in the United States. Data Sources: National Institutes of Health Research Portfolio Online Reporting Tools, Agency for Healthcare Research and Quality Grants On‐Line Database, Health Services Research Projects in Progress, PubMed, Integrated Postsecondary Education Data System, AcademyHealth membership database, and social networks. Study Design: Exploratory descriptive analysis of individuals involved in health services research (HSR) in the United States as of 2015/16. Principal Findings: The HSRer stock grew by 25 percent to 45 percent between 2007 and 2015/16, which was slower than the previous measurement period. The growth in the number of doctoral and master's degrees conferred in core HSR fields has been slowing in recent years. Minorities are underrepresented among HSRers, but this trend may improve over time given the diversity of the educational pipeline. Hispanics, however, were generally underrepresented in the educational pipeline. Conclusions: The average annual growth rate of HSRers appears to be within range of national recommendations. Additional work is needed to assess whether supply of HSRers is meeting demand and to ensure a competent and diverse educational pipeline that meets the needs of an evolving health system.